Study of nonlinear flow mechanisms and microfracture networks in low-permeability reservoirs - Hao, Mingqiang; Liu, Xuewei; Xia, Jing; Liu, Yang (Frontiers in Earth Science, 2023)
Horizontal well and hydraulic fracturing technologies has been widely applied in the world. They significantly improve oil recovery efficiency and yield better economic benefits. During the fluid flow in a reservoir with fractured horizontal wells, nonlinear flow and microfracture networks have been observed in the field and lab. However, the interaction between nonlinear flow and microfracture networks are still not clearly explained. This study applies nonlinear flow experiment and triaxial compression test to analyze nonlinear flow characteristics in the environment of microfracture networks. The results indicate that: (1) with the decrease in pressure gradient, fluid capacity in some capillaries with smaller size decreases, which leads to the appearance of nonlinear flow; (2) microfracture networks shrink nonlinear flow region and improve flow efficiency, which further benefits in the reservoir quality; (3) considering the scale of fracture aperture, microfracture can be considered as parts of matrix pores. But it contributes more to the flow efficiency compared with natural fractures; (4) Microfracture significantly increases rock stress sensitivity and reduce the threshold of permeability to allow fluid flow.